How to find reliable “green” statistical data? - Baszczyńska, Aleksandra; Jędrzejczak, Alina (W poszukiwaniu zielonego ładu, 2022)
The chapter presents the most important issues concerning the organization of statistical research on various phenomena related to climate change and environmental degradation. In particular, all works connected with the collection and analysis of statistical data, aimed directly or indirectly at the analysis of the green economy, are described. An integral part of the study is the presentation of selected statistical databases with the specification of categories and groups of “green” statistical data.